1980
DOI: 10.1083/jcb.84.2.468
|View full text |Cite
|
Sign up to set email alerts
|

Primary induction of vitellogenin synthesis in monolayer cultures of amphibian hepatocytes.

Abstract: Direct induction of vitellogenin production in cultured male amphibian hepatocytes by estradiol-l7ß has been accomplished. Liver cells were isolated from adult male bullfrogs by collagenase perfusion and maintained as monolayers in serumfree medium containing insulin and estradiol . Vitellogenin production was measured by direct immunoprecipitation from radioactively labeled secreted protein with a specific antiserum against vitellogenin . Significant quantities of vitellogenin were detected in the exported pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In oviparous animals, the synthesis of VTG by hepatocytes represent a good system with which to study the mechanism of action of steroid hormones [31][32][33][34]. Most of these studies have used hepatocytes of either amphibians (especially Xenopus laevis) or birds (especially chickens), though some have been based on hepatocytes from fish [24,[35][36][37]. Various techniques have been used to culture fish hepatocytes [35,37].…”
Section: Resultsmentioning
confidence: 99%
“…In oviparous animals, the synthesis of VTG by hepatocytes represent a good system with which to study the mechanism of action of steroid hormones [31][32][33][34]. Most of these studies have used hepatocytes of either amphibians (especially Xenopus laevis) or birds (especially chickens), though some have been based on hepatocytes from fish [24,[35][36][37]. Various techniques have been used to culture fish hepatocytes [35,37].…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, using insulin-containing medium (10 mU/ml) in the primary culture, the synthesis of overall protein, especially secretory proteins, increased with culture time. De-induction of albumin synthesis reported in other primary culture systems (17,19) was not observed under the present conditions. Since albumin synthesis was reduced by estradiol treatment even in the presence of insulin, it is strongly suggested that albumin production is negatively controled by estradiol.…”
Section: Discussionmentioning
confidence: 46%
“…The present procedures for cell culture were similar to those in Rana cutesbeiuna system (17), in which, however, a solution for dispersion of liver cells contained no pyruvate and perfusion was done with a collagenase solution at a higher temperature (40°C). The temperature used for collagenase-digestion was set at 30°C, since the ability of cells become attached to substrutum of the culture dish was reduced by the treatment at a higher temperature.…”
Section: Discussionmentioning
confidence: 92%
“…This number is consistent with the literature mentioned above. It was shown that when E2 was applied to the frog hepatocyte culture, the Vtg fluorescent marking and the Vtg synthesis in the hepatocytes increased over the course of the experiment (Stanchfield & Yager 1980). Van Bohemen, Lambert, Goos and Van Oordt (1982) reported that when E2 and estrone were injected to female rainbow trout (Onchorynchus mykiss), small amounts of Vtg was found to be stored in the liver, and given rapidly to blood 7 days after the injection.…”
Section: Discussionmentioning
confidence: 99%